2012
DOI: 10.1089/gtmb.2011.0163
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Analysis of MTHFR, Factor II, and Factor V Genes in the Pomeranian Population of Espirito Santo, Brazil

Abstract: Pomeranian populations worldwide immigrated originally from the north of Europe, and because of their preferential marriage, religion, and cultural habits, they show little or no reproductive mixing with local populations. Methylenetetrahydrofolate reductase gene (MTHFR) C677T, Factor V Leiden, and Factor II G20210A polymorphisms are linked to augmented clotting and their frequencies may vary according to population ethnicity. We aimed to assess the frequencies of these thrombophilic alleles in the Pomeranian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
4
3
1
Order By: Relevance
“…There was no statistically significant difference in allelic and genotypic distributions between the two populations. This result confirms data of Stur et al [42] which reported gene flow between the general and Pomeranian populations of ES. Numbers in parenthesis represents allele or genotype counts For each SNP, we analyzed the difference in genotype distribution among ES populations and two other populations of different ethnic groups randomly selected and a population of southeast Brazil (Table 6).…”
Section: Discussionsupporting
confidence: 93%
“…There was no statistically significant difference in allelic and genotypic distributions between the two populations. This result confirms data of Stur et al [42] which reported gene flow between the general and Pomeranian populations of ES. Numbers in parenthesis represents allele or genotype counts For each SNP, we analyzed the difference in genotype distribution among ES populations and two other populations of different ethnic groups randomly selected and a population of southeast Brazil (Table 6).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, considerable heterogeneity is expected in the frequency distribution of genetic variants within Brazilian territory. For example, while in a northern Brazilian population the frequency of the FV G1691A and FII G20212A variants was 1.6 (P = 0.248) and 0.8% (P = 0.5), respectively, (Yoshioka et al, 2006) same variants was 4.8 (P = 0.029) and 2% (P = 0.123) (Stur et al, 2012). The former northern findings did not differ significantly from the frequencies found in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…We did not observe the presence of a homozygous genotype for either C282Y or S65C among the studied population, and the heterozygous compound genotype C282Y/H63D was observed in only one sample. The MTHFR mutations showed a prevalence of 44.8% (C/T) and 9.8% (T/T) for C677T and 33.6% (A/C) and 6.1% (C/C) for A1298C, consistent with the results obtained from previous studies in Brazilian children and other control groups [ 22 24 , 26 , 42 ]. A comparison of the results obtained in the present study with those obtained in a recent prevalence study in middle-southern Italian blood donors revealed that the cohort used in this study presented a higher number of wild-type subjects for both C677T and A1298C [ 43 ].…”
Section: Discussionsupporting
confidence: 91%